A novel laboratory test for backward erosion piping. Issue 5 (29th November 2017) - Robbins, Bryant A.; van Beek, Vera M.; López-Soto, Jamie F.; Montalvo-Bartolomei, Axel M.; Murphy, John
Abstract : A new type of laboratory test has been developed for measuring the local hydraulic conditions required for the progression of backward erosion piping, an internal erosion mechanism for water-retaining structures. The device consists of clear acrylic cylinders in which soil samples can be subjected to unidirectional, horizontal flow. The cylindrical sample shape ensures that the eroding pipe passes along the top of the sample allowing for pressure, pipe flow velocity and pipe geometry to be accurately measured in time. Experimental results are presented for tests conducted on two uniformly graded sands. The test results indicate that the critical hydraulic conditions for progression of backward erosion piping remain constant for all scales tested when defined over a distance of 10 cm upstream of the pipe tip. Additionally, the rate of pipe progression was found to be proportional to the seepage velocity upstream of the eroding pipe.